Glyoxalase I (GLX-I) analysis in native maize from Oaxaca, Mexico, infected with Aspergillus flavus in vitro - Varapizuela-Sánchez, Carlos Francisco; Sánchez-Medina, Marco Antonio; Pina-Canseco, María del Socorro; Rosas-Murrieta, Nora Hilda; Pérez-Santiago, Alma Dolores; García-Montalvo, Iván Antonio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The glyoxalase system plays an important role in various physiological processes in plants when they are subjected to different types of stress, whether physical, chemical or biological. Aspergillus flavus is an aflatoxin-producing fungus that contaminates dry grains, leading to a gradual deterioration of the grains and a significant reduction in their nutritional value. The objective of the present study was to evaluate the activity of the enzyme glyoxalase I (GLX-I) in maize coleoptiles from Oaxaca in response to infection caused by Aspergillus flavus. Nine maize samples from four different races were analyzed. The samples were inoculated with a suspension of Aspergillus flavus spores of known concentration and total protein extraction and quantification were performed on the coleoptiles, and GLX-I activity was determined by quantifying the amount of S-lactoylglutathione produced per minute. In addition, analysis of gene expression by reverse transcriptase polymerase chain reaction (RT-PCR) was performed. The inoculated maize coleoptiles showed symptoms of infection, color changes and wilting. The concentration of total proteins decreased significantly in the extracts of four samples in the presence of the fungus. In the GLX-I analysis, two samples had the highest enzymatic activity in the infected coleoptile extract with respect to the healthy one, in addition to presenting greater expression of the gene in the RT-PCR assay, this due to the response to Aspergillus flavus infection.